Pengaruh Stres Kerja dan Motivasi Kerja terhadap Kinerja Tenaga Kesehatan pada Puskesmas Multiwahana Palembang - Annisa Luthfi Shafira; Zunaidah; Nia Meitisari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of work stress and work motivation on the performance of health workers at Multiwahana Palembang Public Health Center. The type of research used is quantitative research with a causal associative method. The population in this study were all health workers at the Multiwahana Palembang Public Health Center totaling 36 people, used as research samples determined using the saturated sampling method. Data collection techniques used were interviews, observation and distributing questionnaires containing questions about work stress, work motivation and performance. The analytical tool used is Multiple Linear Regression Analysis using SPSS 29 for windows program. The results of data analysis show that: (1) work stress has a negative and significant effect on performance, (2) work motivation has a positive and significant effect on performance.